Development of reporter genes for use in gram positive bacteria - Qazi, Saara N. A. (1999)
Green fluorescent protein (gfp) and bacterial luminescence (lux) reporter genes have been used to construct a variety of reporter plasmids for Gram positive bacteria with the aim of using these for bacterial localisation and gene expression studies. The native gfp and luxCDABE genes were cloned into a shuttle vector and the resulting plasmids used to transform Listeria monocytogenes. However, the bacterial populations were found to be weakly fluorescent or luminescent compared to E. coli harbouring the same plasmids.